أثر التفاعل بين التغذية الراجعة وترتيب مفردات الاختبار الإلكتروني على الخصائص السيكومترية للاختبار ومفرداته والتحصيل لدى طلاب الصف العاشر في سلطنة عمان - بادي، بدر حمد حميد
Abstract The study aimed at exploring the effect of the interaction between correctional feedback and patterns of test items ordering according to three formats (i.e. curriculum order, random, and difficulty factor) on the psychometric characteristics of the test and its items, and on student performance. To achieve the aims of the study, an achievement test was constructed on the content of unit one, social studies subject, grade ten, semester one. The test finally consisted of (35) multiple choice items, four options for each. The test items were distributed according to three formats, each of different item position: the first format was according to the order of the curriculum, the second format ordered randomly, and the third format was according to difficulty factor (from easy to difficult.). The study population consisted of all of the grade ten students (286) at the Islamic Institutes of the Sultan Qaboos Higher Center for Culture and Sciences, in the academic year 2020/2021, in six institutes. The sample of the study was the whole population. The results revealed that there were no differences of statistical significance ascribed to correctional feedback presented during the test. It also revealed no differences of statistical significance at the level of (0.05) in student performance due to test items ordering patterns even in the first format (curriculum order) in which students' performance average was better than the other two formats. The study also revealed that there was an effect of interaction between the correctional feedback and the test items ordering patterns; a statistically significant interaction in behalf of the first format (curriculum order), and (11%) of variance in students marks can be ascribed to correctional feedback presented during the test and test items ordering patterns. When studying the psychometric characteristics of the test items in its three formats, the study revealed differences of statistical significance at the level (0.05); the factors of reliability, validity and objectivity of the test items were statistically significant for the first format (curriculum order). However, the study did not reveal differences of statistical significance at the level (0.05) in the factors of reliability and validity of the three tests. The study recommends use of the pattern of ordering test items according to its curriculum content order when constructing achievement multiple choice tests.